CT, MRI and DWI Features of a Solid Organizing Hepatic Abscess. (13th August 2014) - Savastano, Sergio; Pellizzer, Giampiero; Di Grazia, Lorenzo; Giacomini, Dario; Beghetto, Mario
Abstract : Solid organizing hepatic abscess is a rare form of focal infection, which needs differentiation from benign and malignant solid masses. We report a case of a 30-year-old man with a solid organizing hepatic abscess, diagnosed by imaging and ex juvantibus criteria. CT and MRI findings are presented and role of DWI is outlined. Noninvasive diagnosis of a solid organizing hepatic abscess is possible in the appropriate clinical setting; percutaneous or surgical biopsy may be indicated in equivocal cases.